TRANSFORMASI DIGITAL UMKM PARIWISATA DALAM MENDORONG EKONOMI KREATIF BERKELANJUTAN - Tiktik Dewi Sartika,; Adrial, Adrial; Rella Dwi Respati, (Journal of Innovation Research and Knowledge, 2025)
Digitalization in the tourism sector's MSMEs plays a crucial role as a key driver in accelerating the development of the creative economy and enhancing competitiveness. This study aims to analyze how digitalization can support the development of the creative economy in the MSME sector, highlighting the challenges and opportunities faced by business owners. The research employs a qualitative approach through a literature study, examining various secondary sources, such as academic journals, books, and relevant articles. The findings of this study reveal that while digitalization offers significant benefits in expanding markets and improving operational efficiency for MSMEs in the tourism sector, several challenges remain, such as limited access to technology, lack of digital skills, and insufficient market understanding. Therefore, this research recommends providing digital capacity-building training for MSME actors and implementing policy support to facilitate the adoption of technology in the tourism sector